Strategic public housing and foreign direct investment - Kristof Dascher (University College Dublin, Department of Economics, 2002)
We suggest that public housing matters for FDI. We assume that FDI creates gains for some residents and losses for others. Losers from FDI will oppose FDI. To win support for FDI, local government may want to pay compensation in cash. In the paper's model, however, cash payments are not successful. But public housing is. – Ultimately we argue that (1) public housing makes FDI more palatable where (2) cash transfers fail, so that (3) local government may choose to invest into public housing to overcome opposition against FDI.
hdl:10197/1275
Keywords: F23; H42; R23; 330; Public Housing; Foreign Direct Investment; Sozialer Wohnungsbau; Soziale Wohnungspolitik; Direktinvestition; Öffentlicher Transfer; Theorie